Exact solutions for unsteady MHD free convection flow with time dependent shear stress - Khan, Arshad (2014)
In this paper, the effects of MHD on unsteady free convection flow with time dependent shear stress are analyzed. The effects of thermal radiation and porosity on the flow are also studied. Closed-form solutions in general form are obtained by using the Laplace transform technique. The obtained results for velocity and temperature are found to satisfy all the imposed initial and boundary conditions and can be reduced to known solutions from the literature as limiting cases. The velocity profile is presented as a sum of convective and mechanical parts. The effects of shear stress and effective Prandtl number on velocity as well as temperature profiles are presented graphically and discussed in details.